2015
DOI: 10.2105/ajph.2014.302105
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Adapted HIV and Sexually Transmitted Infection Prevention Intervention for Incarcerated Women: A Randomized Controlled Trial

Abstract: Objectives We tested the efficacy of an adapted evidence-based HIV–sexually transmitted infection (STI) behavioral intervention (Providing Opportunities for Women′s Empowerment, Risk-Reduction, and Relationships, or POWER) among incarcerated women. Methods We conducted a randomized trial with 521 women aged 18 to 60 years in 2 correctional facilities in North Carolina in 2010 and 2011. Intervention participants attended 8 POWER sessions; control participants received a single standard-of-care STI prevention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
49
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 29 publications
0
49
0
Order By: Relevance
“…37 Incarcerated women have higher rates of HIV and sexually transmitted infections (STI) than the general population. 38 In 2010, 1.9% of incarcerated adult women in the U.S. were HIV positive which is 13 times the rate of adult women in the general population (0.15%). 39 There are approximately 23,000 HIV infected adult women released from correctional institutions annually in the U.S. with the majority being African American women.…”
Section: Racial Disparity For Hiv-1 Acquisition In African American Wmentioning
confidence: 99%
“…37 Incarcerated women have higher rates of HIV and sexually transmitted infections (STI) than the general population. 38 In 2010, 1.9% of incarcerated adult women in the U.S. were HIV positive which is 13 times the rate of adult women in the general population (0.15%). 39 There are approximately 23,000 HIV infected adult women released from correctional institutions annually in the U.S. with the majority being African American women.…”
Section: Racial Disparity For Hiv-1 Acquisition In African American Wmentioning
confidence: 99%
“…Of the eight studies that were included in the integrative review, five were identified in MEDLINE (25)(26)(27)(28)(29) , one in Cochrane (30) , one in ScienceDirect (31) , and one in CINAHL (32) . Most of the studies were developed in the United States (7) (25)(26)(27)(28)(29)(30)32) and all of them were written in English. Only one article was prepared in Brazil (31) .…”
Section: Resultsmentioning
confidence: 99%
“…Other resources such as videos and games were also used (27)(28)(29)(30) . These technologies can be built and used to boost the teaching and learning process without the need for Internet access, which favors their use in prison settings.…”
Section: Randomized Clinical Trial N=444mentioning
confidence: 99%
“…Among these, 4 HIV interventions explicitly included women-specific and/or trauma-informed content (3942). Project POWER (Providing Opportunities for Women’s Empowerment, Risk-Reduction, and Relationships), for example, was extensively adapted from a CDC evidence-based intervention (EBI) to include HIV disease knowledge, personal risk recognition, evaluation of behavioral change, self-efficacy, and attainment of skills in 9 facilitator-led sessions prior to release (40). Attrition was high post-release but there was still a significant intervention effect on self-reported condom use, knowledge, health-protective communication, and social support compared to a single HIV prevention session as usual.…”
Section: Resultsmentioning
confidence: 99%